Gastrointestinal Fistulas in Necrotizing Pancreatitis Receiving a Step-Up Approach Incidence, Risk Factors, Outcomes and Treatment - Liu Z; Ke H; Xiong Y; Liu H; Yue M; Liu P (Dove Medical Press, 2023)
Zheyu Liu,1 Huajing Ke,1 Yuwen Xiong,1 Hui Liu,1 Mengli Yue,2 Pi Liu3 1Department of Gastroenterology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China; 2Affiliated Longhua People's Hospital, The Third School of Clinical Medicine, Southern Medical University, Shenzhen, People's Republic of China; 3Department of Gastroenterology, Affiliated Longhua People's Hospital, Southern Medical University, Shenzhen, People's Republic of ChinaCorrespondence: Pi Liu, Department of Gastroenterology, Affiliated Longhua People's Hospital, Southern Medical University, Shenzhen, People's Republic of China, Tel +86- 13507913736, Email liupi126@sina.comPurpose: Necrotizing pancreatitis (NP) complicated by gastrointestinal fistula is challenging and understudied. As the treatment of necrotizing pancreatitis changed to a step-up strategy, we attempted to evaluate the incidence, risk factors, clinical outcomes and treatment of gastrointestinal fistulas in patients receiving a step-up approach.Methods: Clinical data from 1274 patients with NP from 2014- 2022 were retrospectively analyzed. Multivariable logistic regression analysis was conducted to identify risk factors and propensity score matching (PSM) to explore clinical outcomes in patients with gastrointestinal fistulas.Results: Gastrointestinal fistulas occurred in 8.01% (102/1274) of patients. Of these, 10 were gastric fistulas, 52 were duodenal fistulas, 14 were jejunal or ileal fistulas and 41 were colonic fistulas. Low albumin on admission (OR, 0.936), higher CTSI (OR, 1.143) and invasive intervention prior to diagnosis of gastrointestinal fistula (OR, 5.84) were independent risk factors for the occurrence of gastrointestinal fistula, and early enteral nutrition (OR, 0.191) was a protective factor. Patients who developed a gastrointestinal fistula were in a worse condition on admission and had a poorer clinical outcome (p< 0.05). After PSM, both groups of patients had similar baseline information and clinical characteristics at admission. The development of gastrointestinal fistulas resulted in new-onset persistent organ failure, increased open surgery, prolonged parenteral nutrition and hospitalization, but not increased mortality. The majority of patients received only conservative treatment and minimally invasive interventions, with 7 patients (11.3%) receiving surgery for upper gastrointestinal fistulas and 11 patients (26.9%) for colonic fistulas.Conclusion: Gastrointestinal fistulas occurred in 8.01% of NP patients. Independent risk factors were low albumin, high CTSI and early intervention, while early enteral nutrition was a protective factor. After PSM, gastrointestinal fistulas resulted in an increased proportion of NP patients receiving open surgery and prolonged hospitalization. The majority of patients with gastrointestinal fistulas treated with step-up therapy could avoid surgery.Keywords: necrotizing pancreatitis, a step-up approach, gastrointestinal fistula, minimally invasive step-up intervention